Konsep Raja Ideal pada Masa Sriwijaya Berdasarkan Bukti-Bukti Tertulis - Muhamad Alnoza (Jumantara: Jurnal Manuskrip Nusantara, 2020)
The king in the Hindu-Buddhist era had such a big role for his people. The ideal king is needed by the people so that the country becomes prosperous. The concept of an ideal king has been known for a long time in the archipelago, even since before Hindu-Buddhist culture developed. In Java and Bali the ideal king is described in the Astabrata Concept. The concept of an ideal king in Srivijaya has never been discussed by researchers, even though Srivijaya was one of the ruling kingdoms in Indonesia during the early Hindu-Buddhist era. This study discusses about concept of the ideal king that developed in Srivijaya based on written data in the form of inscriptions scattered in several conquered Srivijaya areas. The concept of the ideal king of Srivijaya needs to be known to reconstruct how much acceptance of Hindu-Buddhist culture in Indonesia, especially during the Srivijaya era. In answering these problems, research was conducted with archeological methods, which consisted of data collection, analysis and interpretation. Based on this research, it can be seen that the concept of the ideal king of Srivijaya was much influenced by Buddhism, especially the Vajrayana school. The king in Srivijaya depicted as an excellent person, born as a man, diplomat and wealthy.